Artificial intelligence guided physician directive improves head and neck planning quality and practice Uniformity: A prospective study. (May 2023) - Mashayekhi, Maryam; McBeth, Rafe; Nguyen, Dan; Yen, Allen; Trivedi, Zipalkumar; Moon, Dominic; Avkshtol, Vlad; Vo, Dat; Sher, David; Jiang, Steve; Lin, Mu-Han
Highlights: AI dose predictor was fully integrated with treatment planning system and used as a physicain decision support tool to improve uniformity of practice. Model was trained based on our standard of practice, but implemented at the time of expansion with 3 new physicians join the practice. Phase 1 retrospective evaluation demonstrated the non-uniform practice among 3 MDs and only 52.9% frequency planner can achieve physicians' directives. Significant improvement in practice uniformity of practice was observed after utilizing AI as DST and 80.4% frequency clinical plan can achieve AI-guided physician directives.